Matrix metalloproteinase expressions in cultured microglial cells - Nootchanat Mairuae (Chulalongkorn University, 2003)
Alzheimer s disease (AD) is the most common cause of dementia in the elderly characterized by progressive loss of nerve cells in the brain areas associated with learning and memory. A key feature of this disease is the presence of numerous senile plaques composed mainly of an insoluble Aß core surrounded by iron-rich activated microglia. It is believed that progressive cerebral accumulation of Aß is an early and perhaps necessary feature of the disease. These complex processes are thought to mediate by microglia which function as the converter of diffuse plaques to dense core plaques in addition to a key inflammatory mediator in the CNS. Moreover, A -induced neurotoxicity may also occur through these activatedglia. In AD brains, activated microglia viewed histologically as plaque-attacking scavengers would not appear to remove deposited Aß as they did in vitro. Therefore, understanding why microglia ineffectivelyremove plaques in AD brains is crucial for molecular targeting of this disease. Recently, cellular iron status has been shown to modulate microglial inflammatory responses as well as a set offunctional genes identified by microarray analysis (Cheepsunthorn et al., 200la, b). In this thesis works, the effect of iron on microglial functions as brain phagocytes was investigated using an in vitro model of iron loading in a rat microglial cell line HAPI. The results are shown for the first time that iron loading in activated microglia increases the the secretion of MMP-9 and MMP- I, but decreases mRNA expression of MMP-10 and the secretion of MMP- 2. Interestingly, it is found that condition of an intracellular iron loading impairs phagocytic activity of activated microglia. These findings indicate that elevated levels of MMP-9, MMP-1, Aß deposition, and other pathological features in the brains of patients with Alzheimer s disease may be a consequence of the disruption of brain iron metabolism and the activation of microglia.